Knowledge Transfer for Climate Adaptation in Hessian Municipalities: Hurdles, Needs and Tailored Solutions - Rossow, Verena; Friedrich, Thomas (DIE ERDE – Journal of the Geographical Society of Berlin, 2026)
Local administrations are key to implementing climate adaptation but differ widely in readiness and expertise. Growing numbers of knowledge transfer programs aim to support and empower municipal stakeholders. To be most effective, these programs must be tailored to specific target groups. This study illustrates a research-based knowledge transfer process and its potential for municipal climate adaptation in Germany. Expert interviews and a survey of municipal employees in Hesse, Germany, identified knowledge gaps and barriers. We show how tailored knowledge transfer can be achieved and emphasize the need for targeted support and training, offering valuable insights for knowledge transfer practitioners.